Work Efficiency as a Mediator in the Relationship between Transformational Leadership and Career Achievement of Lecturers in Universities in Henan, China - Yu, Cui Ming; Aziz, Nor Azni Abdul; Hassan, Aminuddin (Journal of Ecohumanism, 2024)
This study explores the impact of Transformational Leadership (TL) on Work Efficiency (WE) and career achievement among university lecturers in Henan Province, China. Specifically, it examines how WE mediate the relationship between TL and lecturers’ career achievements. TL, characterised by its ability to inspire and motivate followers, was discovered to drive positive organisational change and enhance goal attainment. This research highlights how institutional factors such as leadership decision-making, employee collaboration, and communication influence career trajectories and contribute to career achievement levels. Key milestones in lecturers’ careers, such as appointments, promotions, tenure, and professional growth in teaching, research, and leadership, were considered. Factors like academic qualifications, research productivity, teaching experience, and scholarly publications were identified as influential. Furthermore, maintaining high WE are crucial for managing workloads and meeting academic responsibilities. Using a sample of 974 lecturers selected through random sampling and data collected via questionnaires, the study applied quantitative analysis to investigate the correlation between TL behaviours, WE, and career achievements. The findings reveal that TL positively affects lecturers’ career achievements, with WE serving as a significant mediating factor. This underscores the importance of TL and efficient work practices in advancing lecturers’ careers and enhancing organisational effectiveness.